Relationship of eating behavior and self-esteem with body image perception and other factors among female college students of University of Delhi - Abhilasha Kapoor; Madhu Kumari Upadhyay; Narinder Kumar Saini (Journal of Education and Health Promotion, 2022)
BACKGROUND: Eating disorders (EDs) can lead to life-threatening nutritional deficiencies whereas self-esteem influences interpersonal relationships and academic performance. Excessive concerns about body image resulting in body dissatisfaction not only affect psychological well-being but also predisposes to disordered eating behaviors. The objective of this study is to assess the eating behavior and level of self-esteem, their relationship with body image perception and also identify factors associated with them among undergraduate female college students. MATERIALS AND METHODS: This cross-sectional study was conducted among 180 female undergraduate students of University of Delhi. Sociodemographic characteristics and anthropometric measurements were recorded. Eating Attitude Test-26, Rosenberg Self-esteem Scale, Contour Drawing Rating Scale and Body Shape Questionnaire 34 were used to assess eating behavior, self-esteem, body image dissatisfaction and body shape concerns, respectively. Both descriptive and inferential statistics were used and binary logistic regression was applied to identify the factors determining high risk eating behavior and low self-esteem. RESULTS: In this study, 27.8% of the study participants were overweight or obese, 30.6% had body shape concerns and 76.7% had body image dissatisfaction. Significant proportion (13.9%) of the participants was identified as high risk for the development of EDs and having low self-esteem (12.8%). Body shape concern and family influences were significant predictors of high risk eating behavior whereas type of college and family influences significantly predicted low self-esteem. CONCLUSIONS: The study concluded that factors such as nutritional status, family influences, type of college and body shape concerns lead to high risk eating behavior and low self-esteem. These findings will help in creating awareness on importance of concept of positive body image, healthy weight control behaviors and in developing future interventions.